Formation processes and evolution of Holocene sediments in the Yangtze offshore area: A review and new interpretation on the response to sea-level rise and deltaic progradation. (10th October 2018) - Xu, Taoyu; Shi, Xuefa; Liu, Shengfa; Qiao, Shuqing; Wang, Guoqing; Wang, Xin; Yao, Zhengquan; Yang, Gang; Fang, Xisheng; Li, Xiaoyan; Wu, Yonghua
Abstract: Seismic profiles integrated with borehole cores from offshore of the Yangtze River Delta characterize three distinctive Holocene deposition units in correspondence to estuarine, shallow marine and prodelta facies respectively (Units Ⅰ to Ⅲ). Sedimentary processes and evolution of three units in response to sea-level rise and Yangtze delta development was studied. Estuarine facies occurred as a cluster of mud ridges (unit Ⅰ) was considered to be formed during the later stage of the period ∼10-8 cal ka BP with the prevalence of tidal erosion processes. At the same time however, the area south of the ridge field experienced rapid deposition, possibly due to shelter effects of the Zhoushan Archipelago. Unit Ⅱ, characterized by homogeneous mud composition, rapid accumulation rates and a seaward dipping structure, indicated a gravity flow deposition most likely related to the wave and/or tidal current induced fluid mudflows during the period of ∼ 8-5 cal ka BP. Intrusion of a mud diapir during ∼5-3 cal ka BP related to gravity subsidence localized near the river mouth, lead to deformation of unit Ⅱ. During the ∼3 ka to present, the delta advanced to the study area, depositing subaqueous clinoform (unit Ⅲ). Meanwhile, erosional processes dominated by tidal currents were promoted by the southeastward progradation of the delta. Sediments deposited in the north of the area were transformed into tidal sand ridges. We predict that the delta will likely reduce in area with a further progradation in the recent future.